Look what you made me do : a novel - Lanchester, John (W. W. Norton & Company, 2026)
""Every successful marriage has its own private language." So it is for baby boomer Kate and her beloved architect husband Jack, thirty years into their seemingly idyllic metropolitan North London life. And so it is for spiky millennial screenwriter Phoebe and her charming loafer of a partner, Tony. But when Phoebe's steamy television series Cheating becomes the year's most talked-about show, Kate thinks she sees in it details and intimacies of her marriage that only she and her husband could possibly have known. Who has betrayed whom? Who has stolen whose story--and why? A black comedy of love, trust, resentment, and entitlement, Look What You Made Me Do is the sharply observed and suspenseful story of two very different women from two very different generations, entangled in a battle only one of them can win."--Amazon.